OPTIMALISASI EFEKTIVITAS DAN EFISIENSI DALAM MANAJEMEN RANTAI PASOK AGROINDUSTRI BUAH: TINJAU LITERATUR DAN ARAH RISET MENDATANG - Dimas Hardiansyah Dimas Hardiansyah (Journal of Optimization System and Ergonomy Implementation, 2025)
Agroindustry supply chain management involves several integrated supply chain members from upstream to downstream in a sustainable. The main aspects that need to be considered are performance, added value, risk, improving effectiveness and efficiency in the supply chain management. The purpose of this study was to analyze the supply chain performance, added value, and risk used to effectiveness and efficiency improvement of fruit agroindustry supply chain management. A search for scientific articles published from 2005 to 2020 was conducted. There were 94 scientific articles reviewed into five classifications, i.e. apple supply chain management, supply chain performance, added value, supply chain risk, effectiveness and efficiency. So far, there has been little discussion about increasing the effectiveness and efficiency of supply chain management in the fruit agorindustry and has not been carried out comprehensively. The scientific articles obtained were examined into several analyzes of approaches and methods so that models could be developed to improve effectiveness and efficiency of supply chain management. In the future, a combination of several methods and implementations of information technology can be used to effectiveness and efficiency improvement of fruit agroindustry supply chain management.